Experience of Using Ursodeoxycholic Acid in Children with Organic Diseases of the Liver - Ye.N. Babadzhanian (Zaslavsky O.Yu., 2015)
The mechanisms of ursodeoxycholic acid effects on the human body, the findings of clinical studies and observations on the use of ursodeoxycholic acid preparation for the treatment of children with organic diseases of the liver were considered.